PENGARUH ZAKAT, INFAK DAN SHODAQOH (ZIS) PRODUKTIF TERHADAP KINERJA UMKM YANG TERDAMPAK PANDEMI COVID-19 (Studi Kasus UMKM Binaan LAZIZNU Kertosono) - Bayu Kurnia Rizki; Nur Diana; Harun Alrasyid (Fakultas Ekonomi dan Bisnis Universitas Islam Malang, 2021)
This study aims to determine the effect of Productive Zakat, Infaq and Shodaqoh (ZIS) on the performance of MSMEs affected by the Covid-19 pandemic. Samples were taken using purposive sampling method. The method used in this research is descriptive quantitative method with simple linear regression analysis technique and hypothesis testing with SPSS. The results of data analysis show that Productive ZIS simultaneously affects the performance of MSMEs affected by the COVID-19 pandemic. Partially, productive ZIS affects the performance of MSMEs affected by the COVID-19 pandemic.